Neutralization, by a monospecific Bothrops lanceolatus antivenom, of toxic activities induced by homologous and heterologous Bothı́rops snake venoms - Bogarín, Guisella (1999)
A monospecific Bothrops lanceolatus antivenom, currently used in Martinique, was tested for its efficacy in the neutralization of several toxic and enzymatic activities of the venoms of B. lanceolatus, B. atrox and B. asper. When tested by the i.p. route in mice, B. lanceolatus venom had an LD50 of 12.8 microg/g. In addition, it induced local tissue damage (hemorrhage, edema and myotoxicity) and showed indirect hemolytic activity, but was devoid of coagulant effect on human plasma in vitro and of defibrinating activity in mice. Antivenom was fully effective in the neutralization of lethal, hemorrhagic, edema-forming, myotoxic and indirect hemolytic effects of B. lanceolatus venom in assays involving preincubation of venom and antivenom. When tested against the venoms of B. asper and B. atrox, the antivenom completely neutralized the lethal, hemorrhagic, myotoxic and indirect hemolytic effects, and was partially effective in neutralizing edema-forming activity. In contrast, the antivenom was ineffective in the neutralization of in vitro coagulant and in vivo defibrinating effects induced by these two venoms.